The Effects Of Core Values Towards The Organisation Reputation: The Mediator Role Of Social Media Reputation - Othman, Mohd Zailani (2023)
In today’s business world, the reputation of the organisation is becoming increasingly important, especially for well-known and well-established organizations, since business is built on reputation. However, the rise of social media, which enables instantaneous global communications, makes it more difficult for organizations to manage their reputation in the marketplace. It is a significant challenge for organizations to protect and maintain their reputation since damage to the reputation of the organisation may result in the loss of shareholder trust, consumer confidence, and revenue loss which affects their performance and loss of their competitiveness. Reputation derives from core values because an organisation’s identity and core values are the foundation for a positive reputation. Thus, organizations must consider the core values of social media variables such as transparency, trust, engagement, and authenticity that affect their reputation. Drawing upon the Resource-Based View (RBV) Theory, a conceptual framework is developed for further investigation. A quantitative approach was employed to achieve the objectives of the study. This study examined the relationships between social media usage as the antecedent variable, core values of transparency, trust, engagement, and trust as the independent variables and the reputation of the organisation as the dependent variable. The study also assessed the mediating effect of the reputation of social media on the relationships between core values and the reputation of the organisation.